KANDUNGAN PROTEIN KASAR, KALSIUM, DAN FOSFOR TEPUNG LIMBAH UDANG SEBAGAI BAHAN PAKAN YANG DIOLAH DENGAN ASAM ASETAT (CH3COOH) - Wowor, Andre R.Y.; Bagau, B.; Untu, I; Liwe, H (Universitas Sam Ratulangi, 2015)
THE EFFECT OF UTILIZATION OF ACETIC ACID (CH3COOH) SOLUTION IN SHRIMP WASTE MEAL PROCESSING AS A FEED ON CRUDE PROTEIN, CALCIUM AND PHOSPHORUS CONTENT.An experiment was conducted to determine the effect of different level of acetic acid solution in the processing of shrimp waste meal. Shrimp waste material was in the form of leftover meat, skin, head, and other unutilized parts of shrimp. Research was arranged using Completely Randomized Design (CRD) with 4 treatments: A0 = distilled water without acetic acid solution, A1 = 5% acetic acid solution, A2 = 10% acetic acid solution, and A3 = 15% acetic acid solution. Each treatment was replicated 4 times. Tukeyâ€™s test was employed to analyze treatment differences. Variable measured were: crude protein, calcium, and phosphorus content of shrimp waste. Research result showed that acetic acid solution level significantly affect protein, calcium, and phosphorus content of shrimp waste. Crude protein content of A2 was significantly (P < 0.05) higher compared with A0, A1, and A3, but significantly (P < 0.05) reduced calcium and phosphorus content of shrimp waste meal at the higher level. It can be concluded that utilization of 10% acetic acid solution in shrimp waste meal processing gave the best result with protein content of 56,37%, calcium 2,98%, and phosphorus 0,98%. Keywords :Shrimp waste meal, Acetic acid solution, Protein, Calcium, Phosphorus Â Â